Burying Earth's Primitive Mantle in the Slab Graveyard. (19th March 2021) - Jones, T. D.; Sime, N.; van Keken, P. E.
Abstract: The evolution of mantle composition can be viewed as a process of destruction whereby the initial chemical state is overprinted and reworked with time. Analyses of ocean island basalts reveals that some portion of the mantle has survived this process, retaining a chemically "primitive" signature. A question that remains is how this primitive signature has survived four and a half billion years of vigorous convection. We hypothesize that some of Earth's primitive mantle is buried within a slab graveyard at the core‐mantle boundary. We explore this possibility using high‐resolution finite element models of mantle convection, in which oceanic lithosphere is produced at zones of plate spreading and subducted at zones of plate convergence. Upon subduction, dense oceanic crust sinks to the base of the mantle and gradually accumulates to form broad, robust thermochemical piles. Sinking oceanic crust entrains the surrounding mantle whose composition is predominantly primitive early in the model's evolution. As a result, thermochemical piles are initially supplied with relatively high concentrations of primitive material—summing up to ∼30% their total mass. The dense oceanic crust dominating the piles resists efficient mixing and preserves the primitive material that it is intermingled with. The significance of this process is shown to be proportional the rate of mantle processing through time and the excess density of oceanic crust at mantle pressures and temperatures. Unlike other theories for the survival of Earth's primitive mantle, this one does not require the early Earth to have large‐scale domains of anomalously high density and/or viscosity. Plain Language Summary: When oceanic plates pull apart the mantle melts to form slabs of lithosphere, which are later recycled back into the mantle at subduction zones. This process of melting and subduction destroys the initial chemical signature of the mantle. Geochemical analyses reveal that some portion of the mantle has avoided this process and retained a chemically "primitive" signature. How this material has survived vigorous convection for ∼4.5 Gyr is an open question. Here we propose that it may be preserved at the base of the mantle in large accumulations of subducted lithosphere. These accumulations are dominated by dense oceanic crust but can comprise up to 30% primitive material. The intermingling of oceanic crust and primitive material may explain why the chemical signatures of both coexist in volcanic eruptions at Earth's surface. Key Points: Subducting oceanic lithosphere entrains primitive mantle as it sinks to the core‐mantle boundary Dense oceanic crust forms robust thermochemical piles that can trap and preserve primitive material over the age of the Earth The mixture of primitive and recycled material may explain the co‐existence of these signatures observed in ocean island basalts